Nephrectomy for a case of intrarenal dermoid cyst: was it an appropriate decision? - Goh EH; Christopher CKH; Praveen S; Tan GH; Rozman Z; Zulkifli MZ; Badrulhisham B (Department of Surgery, UKM Medical Centre, 2011)
Dermoid cyst in a kidney is rarely seen. We report a case of intrarenal dermoid cyst which mimics malignant renal tumour and discuss the dilemma in managing this disease.